2012
DOI: 10.1007/s10620-012-2393-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of NDRG2 in Gastric Cancer and Its Clinical Significance

Abstract: Our results suggest that the aberrant methylation of NDRG2 may be mainly responsible for its downregulation in gastric cancer, and may play an important role in the metastasis of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…In accordance with previous studies3031, methylation of the NDRG2 promoter was found in various cancer types (Supplementary Table 7; Fig. 7a).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies3031, methylation of the NDRG2 promoter was found in various cancer types (Supplementary Table 7; Fig. 7a).…”
Section: Resultssupporting
confidence: 92%
“…The phosphorylation of Ser380/Thr382/Thr383 is also elevated in human fibromyomatous uteri and may be a contributory factor in the development of uterine leiomyomas47. Although it is not known whether these phosphorylation events are attributed to the functional inactivation of NDRG2 , decreased expression and promoter methylation of the NDRG2 gene have been reported in various types of cancer, such as liver cancers, gastric cancers, colon cancers and glioblastomas303148495051. Therefore, we hypothesize that in ATLL and other types of tumour cells without genetic alterations in the PI3K-AKT pathway, the suppression of NDRG2 transcription disrupts the negative regulation of PI3K-AKT signalling via sustained PTEN-Ser380/Thr382/Thr383 phosphorylation during tumour development (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have determined 14-20% NDRG2 methylation frequency in grade I-III gliomas, whereas methylation markedly increased to 49 % in grade IV glioblastomas (Figure 1A). In addtion to studies in glioblastoma, a number of studies using various techniques have shown frequent NDRG2 promoter methylation in different cancer cell lines and tumor tissues such as anaplastic meningiomas (20%), liver cancer (77%), colon cancer (27%), oral squamous cell carcinoma (62%), colorectal (64%) and gastric cancer (54%) 4, 13, 24-27. NDRG2 promoter methylation was observed to be associated with higher malignancy grade in meningiomas, colon cancer, gastric cancer and, in agreement with our findings, in glioma tumors 4, 5, 24, 27.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies using various techniques have shown that epigenetic silencing of the NDRG2 promoter has been found in the majority of primary tumors, and different cancer cell lines and other tumor tissues such as glioma (46.3 - 62%), primary gastric (54%) and colorectal carcinoma (64.28%) cancers [811]. NDRG2 promoter methylation was observed to be associated with the invasiveness in gastric and colorectal cancer and with the aggressiveness of glioma tumor [810]. However, our analysis has hown no significant association between NDRG2 gene methylation and pituitary adenoma invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Also, NDRG2 upregulation was associated with Alzheimer's disease or cerebral ischemia [21, 22]. Several studies have shown NDRG2 promoter CpG island methylation and down-regulation in liver [13], gastric [10], colorectal cancers (CRC) [23, 24], glioblastomas [8, 9] and anaplastic meningioma [25]. However, NDRG2 promoter methylation and mRNA expression levels in PAs has not been investigated.…”
Section: Introductionmentioning
confidence: 99%